Massive Pleural Effusion as a Rare Manifestation in Severe Neonatal Sepsis - Lukmasari, Adriana; Trialimas, Jeffry; Taqwim, Wim Khairu; Pramana, Cipta (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Neonatal sepsis can be severe and has mortality rate. The pleural effusion is a rare sign of severe sepsis in newborn and only few studies that reported it. CASE PRESENTATION: We report a case of newborn who referred to our hospital because of dependent mechanical ventilator and severe sepsis. We found a massive pleural effusion and did the pleural drainage. After the drainage, the baby was extubate and discharge well with no signs of respiratory distress. CONCLUSION: Massive pleural effusion might be considered as a cause of dependent ventilator in severe neonatal sepsis.